2010
DOI: 10.1002/app.32737
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic depolymerization of PET waste in a microwave reactor

Abstract: Recycling of waste PET bottles was examined using glycolytic depolymerization with diethylene glycol, under microwave irradiation. The objective was to investigate if depolymerization using microwave energy could provide the same product distribution, while carried out in milder experimental conditions and/or shorter reaction times, resulting, thus besides to polymer recycling, in substantial energy saving. The reaction was carried out in a sealed microwave reactor in which the pressure and temperature were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 32 publications
3
74
0
3
Order By: Relevance
“…Degradation of PET in a microwave reactor was also examined by the group of Achilias and collaborators using four different chemical reagents [29][30][31][32]. Initially, hydrolytic depolymerization in an alkaline solution was investigated [29].…”
Section: Poly(ethylene Terephthalate)mentioning
confidence: 99%
See 1 more Smart Citation
“…Degradation of PET in a microwave reactor was also examined by the group of Achilias and collaborators using four different chemical reagents [29][30][31][32]. Initially, hydrolytic depolymerization in an alkaline solution was investigated [29].…”
Section: Poly(ethylene Terephthalate)mentioning
confidence: 99%
“…Subsequently, glycolysis of PET with DEG was investigated in a microwave reactor [30]. The main degradation product, analyzed and identified by Fourier transform infrared (FTIR) spectroscopy, was an oligoester diol.…”
Section: Poly(ethylene Terephthalate)mentioning
confidence: 99%
“…Research efforts have thus lead to numerous applications in material processing techniques that have resulted in shorter reaction times and greater convenience. Microwave assisted recycling of PET has been also the subject of some investigations [26][27][28][29][30][31][32][33][34][35] reviewed in Ref. [34].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, continuing our previous work on microwave assisted recycling of PET [33][34][35], depolymerization of PET waste, taken from common soft drink bottles, was subjected to methanolysis with methanol and zinc acetate catalyst in a lab-scale microwave reactor in order to study the effect of microwave irradiation on the reaction kinetics. The reaction was carried out in a sealed microwave reactor in which temperature was controlled and continuously recorded together with pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The facts that the polymer depolymerizations could be accelerated by microwave irradiation, and that the depolymerization mechanism was a combination of regular and random chain scissioning have generally been accepted. [7][8][9][10][11] In terms of the applications of microwave irradiation, some of the kinetic processes of PET depolymerization have been studied, such as glycolytic and aminolytic depolymerizations of PET in a microwave reactor, which were conducted by Achilias et al 12,13 The activation energy (E a ) of the depolymerization reactions was evaluated by a simple kinetic model. Moreover, Achilias et al 14 reported the hydrolytic depolymerization of PET in an alkaline solution with a phase-transfer catalyst under microwave irradiation, and the E a was also evaluated.…”
Section: Introductionmentioning
confidence: 99%